Research progress on macrophage metabolic regulation in wound healing of diabetes mellitus type 2 - HUANG Yinghe; ZHAO Guanyu; SUN Yang; HOU Jianji; ZUO Yong (Shanghai Jiaotong Daxue xuebao. Yixue ban)
The global prevalence of diabetes among adults is increasing year by year, with diabetes mellitus type 2 (T2DM) being the most common form. T2DM is a chronic disease characterized by insulin resistance and insufficient insulin secretion, often accompanied by disturbances in glucose, protein, and lipid metabolism. Impaired wound healing is one of the major complications of T2DM. Studies have shown that wound healing in T2DM patients are regulated by macrophages and are closely related to their phenotype, activity, and abundance. Macrophages of different phenotypes play distinct roles in various stages of T2DM wound healing: M1 macrophages are involved in the early inflammatory response and pathogen clearance, while M2 macrophages contribute to anti-inflammatory responses and wound repair during later stages. Dysregulation of macrophage phenotype switching affects wound inflammatory response, skin cell function, and extracellular matrix (ECM) synthesis, ultimately leading to impaired healing. Significant progress has been made in understanding the interactions between macrophage metabolic changes and phenotype switching, and this dynamic relationship might play a synergistic role in regulating the wound healing process in T2DM. This review summarizes the functional roles of macrophages in both normal and T2DM-associated wound healing, discusses alterations in glucose, lipid, and amino acid metabolism in macrophages under pathological conditions, and explores how these metabolic shifts regulate wound healing. Furthermore, it examines the therapeutic potential of targeting macrophage metabolism to improve wound healing outcomes.